Evolusi Regulasi Energi Baru Terbarukan: Analisis Perubahan Orientasi Aturan PLTS Atap - Muhammad Rausyan Fikry; Irwan Triadi (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
. The evolution of regulations related to Rooftop Solar Power (PLTS) utilization in Indonesia reflects changes in the government's approach to solar energy usage. From the Minister of Energy and Mineral Resources Regulation No. 49 of 2018, which underwent several revisions, to the issuance of Minister of Energy and Mineral Resources Regulation No. 2 of 2024, there has been a significant transformation in policy orientation. While initially aimed at promoting the adoption of Rooftop Solar Power at the community level, the latest regulations emphasize more on governance and the overall development of the renewable energy industry. The removal of incentives, such as the electricity export-import mechanism and adjustments in carbon economy regulations, may have negative impacts on the economy and attractiveness of Rooftop Solar Power for the public. However, these adjustments also have the potential to create a more robust ecosystem for the overall growth of the renewable energy industry. As part of efforts towards achieving national renewable energy targets, these regulatory adjustments are expected to encourage innovation in more environmentally friendly energy technologies and increase public participation in the transition towards more sustainable energy sources.